Are New Inpatient Admissions to a Psychiatric Hospital Having the Correct Blood Tests Performed in a Timely Fashion, in Accordance With RCPsych Guidelines? - Jack Bowman (BJPsych Open)
Aims: Severe mental illness (SMI) can have a profound effect on one’s physical health. There are proven long-term effects on morbidity, mortality and total life expectancy for those living with SMI. To address this the Royal College of Psychiatrists (RCPsych) set out a standard in the publication “Standards for Inpatient Mental Health Services” that new inpatient admissions should have routine blood tests performed within 24 hours, unless they have had a recent blood test. NHFT has also adopted this view, as they have set out the same standard in “CLPr041 – Procedure for Physical Healthcare for Patients with Severe Mental Illness”. The aim of this audit was to review whether blood tests were performed within 24 hours of admission, and whether tests performed in the admission set complied with trust recommendations for physical health monitoring.